Interleukin‐17 and interleukin‐22 promote tumor progression in human nonmelanoma skin cancer. Issue 3 (16th January 2015) - Nardinocchi, Lavinia; Sonego, Giulio; Passarelli, Francesca; Avitabile, Simona; Scarponi, Claudia; Failla, Cristina Maria; Simoni, Stefano; Albanesi, Cristina; Cavani, Andrea
<x xml:space="preserve">Abstract</x> Interleukin‐17 (IL‐17) and IL‐22 have been reported to play critical roles in autoimmunity and inflammation but information about their role in cancer is limited. In this study, we investigated the role of IL‐17 and IL‐22 in the progression of human skin basal‐cell carcinoma (BCC) and squamous‐cell carcinoma (SCC). We found that both tumor types are infiltrated with an high number of IL‐17+ and IL‐22+ T lymphocytes, as demonstrated by immunohistochemistry and by FACS analysis performed on peritumoral T‐cell lines isolated from skin biopsies. In vitro studies demonstrated that proliferation and migration of the BCC‐ and SCC‐cell lines M77015 and CAL27 were increased by IL‐17 and IL‐22. Moreover, IL‐17, alone or in combination with TNF‐α, was able to induce the production of two cytokines important for tumor progression, IL‐6 and IL‐8, in CAL27. We also showed that IL‐17 upregulated NF‐κB signaling, while IL‐22 activated the STAT3 pathway and the antiapoptotic AKT protein in M77015 and CAL27. Finally, in vivo experiments demonstrated that IL‐17 and IL‐22 enhanced tumor growth in nude mice injected with CAL27. Altogether, our findings indicate that high levels of IL‐22 and IL‐17 in the BCC and SCC microenvironment promote tumor progression.